1996
DOI: 10.1126/science.271.5249.665
|View full text |Cite
|
Sign up to set email alerts
|

IRS-1-Mediated Inhibition of Insulin Receptor Tyrosine Kinase Activity in TNF-α- and Obesity-Induced Insulin Resistance

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is an important mediator of insulin resistance in obesity and diabetes through its ability to decrease the tyrosine kinase activity of the insulin receptor (IR). Treatment of cultured murine adipocytes with TNF-alpha was shown to induce serine phosphorylation of insulin receptor substrate 1 (IRS-1) and convert IRS-1 into an inhibitor of the IR tyrosine kinase activity in vitro. Myeloid 32D cells, which lack endogenous IRS-1, were resistant to TNF-alpha-mediated inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
1,619
7
72

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,433 publications
(1,755 citation statements)
references
References 18 publications
57
1,619
7
72
Order By: Relevance
“…Cell culture experiments have demonstrated that insulin-induced tyrosine phosphorylation of the β-subunit of the insulin receptor and IRS-1 are reduced in the presence of TNF-α [3,27]. TNF-α promotes serine phosphorylation of IRS-1, which interferes with insulin-induced tyrosine phosphorylation and subsequent insulin signalling and action [28,29]. Data on the dietary intervention used in the current study are consistent with the amelioration of such inhibitory effects.…”
Section: Dietary Interventionsupporting
confidence: 74%
“…Cell culture experiments have demonstrated that insulin-induced tyrosine phosphorylation of the β-subunit of the insulin receptor and IRS-1 are reduced in the presence of TNF-α [3,27]. TNF-α promotes serine phosphorylation of IRS-1, which interferes with insulin-induced tyrosine phosphorylation and subsequent insulin signalling and action [28,29]. Data on the dietary intervention used in the current study are consistent with the amelioration of such inhibitory effects.…”
Section: Dietary Interventionsupporting
confidence: 74%
“…Our results show that increased serine phosphorylation of IR, IRS-1 and IRS-2 could be one of these mechanisms. Previous studies clearly showed that an increase in IR and IRSs serine phosphorylation could induce insulin resistance, pointing to this as an important mechanism in the control of insulin signalling [45,46,47]. It has been reported that activation of PKC induces serine phosphorylation of IR, which can inhibit its tyrosine kinase activity, leading to a decrease in insulin-induced PI3-kinase activity [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…TNF is known to reduce adipose tissue mass by decreasing PPARG production, stimulating lipolysis and repressing genes involved in the uptake and metabolism of lipids and glucose [37][38][39][40][41]. Considering all this, the higher insulin sensitivity that we observed in our study in WAT and that was associated with higher expression of genes mediating insulin sensitivity (Irs1, Slc2a4, adiponectin) and lipogenesis (Srebf1, Fasn, Pparg) may be secondary to the tissue TNF and IL1B depletion, and might contribute to the increase in adipocyte volume seen in C3H/HeJ mice despite lower food intake.…”
Section: Discussionmentioning
confidence: 99%